Company Performance Analysis with Organizational Learning as a Mediating Variable Studies - Prihatin Tiyanto Priagung Hutomo; Frans Sudirjo (Politeknik APP Jakarta, 2023)
This study aimed to determine the effect of Employee Engagement, Knowledge Management and Organizational Learning on the Performance of the Metal Industry in Tegal Regency, especially in Kramat District, Central Java. The population in this study was the metal industry with a total of 121 units with a total workforce of 382 people. The results of the study found that Employee Engagement, Knowledge Management, and Organizational Learning simultaneously had a significant effect on organizational performance. Partially, Employee Engagement had a negative and insignificant effect on Organizational Learning and Organizational Performance. Knowledge Management had a positive and significant effect on Organizational Learning. Organizational learning has a positive effect on organizational performance. However, Organizational Learning was not able to Mediate Employee Engagement on Organizational Performance